E-Loyalty Model Based On E-Service Quality, E-Trust And E-Satisfaction On Gojek Consumers In East Jakarta - Sri Widodo; Sri Yanthy Yosepha (International Journal of Artificial Intelligence Research, 2022)
This study aims to analyze the direct and indirect effects of e-service quality, e-trust, and e-satisfaction on the e-loyalty of Gojek consumers in east Jakarta. This study uses a quantitative approach and survey methods. The population of this research is 100 Gojek consumers in East Jakarta. With purposive sampling technique and the Slovin formula, a sample of 85 people was obtained. Data collection using a questionnaire was measured by a Likert scale. Data analysis used descriptive analysis and path analysis with SPSS version 25.0 for windows. The results showed: e-service quality has a direct positive and significant effect on e-loyalty by 45.2%; e-trust has a positive and significant direct effect on e-loyalty by 25.8%; e-satisfaction has a positive and significant direct effect on e-loyalty by 18.0%; e-service quality has a positive and significant direct effect on e-satisfaction by 34.2%; e-trust has a direct positive and significant effect on e-satisfaction by 33.3%; e-satisfaction is able to mediate the effect of e-service quality on e-loyalty; e-satisfaction is able to mediate the effect of e-trust on e-loyalty of Gojek consumers in East Jakarta